Meconium Aspiration Syndrome: A Narrative Review - Chiara Monfredini; Francesco Cavallin; Paolo Ernesto Villani; Giuseppe Paterlini; Benedetta Allais; Daniele Trevisanuto (MDPI AG, 2021)
Meconium aspiration syndrome is a clinical condition characterized by respiratory failure occurring in neonates born through meconium-stained amniotic fluid. Worldwide, the incidence has declined in developed countries thanks to improved obstetric practices and perinatal care while challenges persist in developing countries. Despite the improved survival rate over the last decades, long-term morbidity among survivors remains a major concern. Since the 1960s, relevant changes have occurred in the perinatal and postnatal management of such patients but the most appropriate approach is still a matter of debate. This review offers an updated overview of the epidemiology, etiopathogenesis, diagnosis, management and prognosis of infants with meconium aspiration syndrome.